PATTERNS OF GENDER RELATIONS ON WOMEN MIGRANT WORKERS FAMILY IN THE PEKALONGAN REGENCY - Aminullah, Fikri (MUWAZAH, 2015)
This Qualitative research of gender perspective, departing from the issue of the high divorce family female migrant workers, which is indicated by a shift in the pattern of gender relations in their family. The research location in Pekalongan. Determination of informants using purposive, developed with snowball. The collection of data through observation, interviews and document study. Analysis techniques using Interaktive Model. Checking the validity of the data using triangulation. The results showed that, shifting patterns of gender relations within the family women migrant workers occur because of, the economic base into the hands of his wife and cultural influences from abroad where women migrant workers work. The structure of the shift pattern of gender relations within the family women migrant workers are categorized in several models, namely: structural shift from vertical patriarchis to horizontal relationship; from the vertical patriarchis to vertical matriarkhis and; from horizontal relationship to vertical matriarkhis. The nature of the shift there are revolutionarily and evolutionary or dynamic equilibrium.Penelitian kualitatif berperspektif gender ini, berangkat dari isu tentang tingginya perceraian keluarga perempuan pekerja migran, yang terindikasi oleh suatu sebab, yaitu pergeseran pola relasi gender dalam keluarga mereka. Teori yang digunakan adalah, teori strukrural- fungsional dan transmisi budaya. Lokasi penelitian di Kabupaten Pekalongan. Penentuan informan menggunakan purposive, dikembangkan dengan snowball. Pengumpulan data menggunakan observasi, wawancara dan studi Dokumen. Teknik analisis menggunakan model Harvard, dengan proses Interaktive Model. Pengecekan validitas data menggunakan triangulasi. Hasil penelitian menunjukan bahwa, pergeseran pola relasi gender dalam keluarga perempuan pekerja migran terjadi karena, adanya basis ekonomi yang beralih ke tangan isteri dan pengaruh budaya dari luar negeri dimana perempuan pekerja migran bekerja. Struktur pergeseran pola relasi gender dalam keluarga perempuan pekerja migran dikategorikan dalam beberapa model, yaitu: struktur pergeseran dari vertikal patriarkhis ke horisontal relationship; dari vertikal patriarkhis ke verikal matriarkhis dan; dari horisontal relationship ke vertikal matriarkhis. Sifat pergeserannya ada yang revolutif dan evolutif atau dynamic equilibrium.